Climate Predicts UV Floral Pattern Size, Anthocyanin Concentration, and Pollen Performance in Clarkia unguiculata - Peach, Kristen; Liu, Jasen W.; Mazer, Susan J. (Frontiers in Plant Science, 2020)
Given that flower size and pigmentation can mediate plant–pollinator interactions, many studies have focused on pollinator-driven selection on these floral traits. However, precipitation, temperature, and solar radiation also contribute to geographic variation in floral traits within multiple species. Several studies have described an ecogeographic pattern in which (within species) high temperature, high ultraviolet (UV) radiation, low precipitation and/or low latitudes are associated with increased floral anthocyanin production, smaller flowers, and/or larger UV-absorbing floral patterns (nectar guides or bull’s eyes). UV floral pattern size has also been shown to provide direct fitness advantages under high UV conditions by protecting developing pollen from cellular damage from UV light. In this study, we tested and corroborated several predictions for how the abiotic environment may directly or indirectly shape geographic patterns of floral color, pattern, and size in Clarkia unguiculata (Onagraceae). This study provides the first report of geographic variation in multispectral floral color and pattern in C. unguiculata, while also providing an experimental test of the putative protective role of UV absorption for pollen performance. We quantified geographic variation among greenhouse-raised populations in UV floral pattern size, mean UV petal reflectance, anthocyanin concentration, and petal area in C. unguiculata across its natural range in California and, using 30 year climate normals for each population, we identified climatic and topographic attributes that are correlated with our focal floral traits. We examined pollen performance under high and low UV light conditions to determine the protective function (if any) of UV floral patterns in this species. Contrary to our expectations, UV nectar guide size was largest in high latitude, low solar UV populations. Estimated floral anthocyanin concentration was highest in populations at low latitudes and with high UV radiation, which does support our predictions. The size of the UV nectar guide did not affect pollen performance in either of the light treatments used in this study (contrary to our predictions). Our results only partially align with expected ecogeographic patterns in these floral traits, highlighting the need for research in a wider range of taxa in order to resolve broad scale patterns of floral color variation.